A Rare Case of Nasal Sarcoma with BCOR Internal Tandem Duplication Showing Complete Pathologic Response to the VDC-IE Chemotherapy Protocol - Samer Salah; Maher A. Sughayer; Omar Jaber; Nebras Abu Abed; Fatena Ajlouni; Wisam Al Gargaz; Ramiz Abu Hijlih; Fawzi Abuhijla; Akram Al-Ibraheem; Farah Alul; Walid Naser (Case Reports in Oncological Medicine)
Sarcoma with BCOR genetic alteration is an exceptionally rare and emerging subtype of sarcoma. It is categorized into two types: BCOR-related gene fusions such as BCOR::CCNB3 sarcomas and other BCOR-rearranged sarcoma and sarcomas with internal tandem duplication of BCOR genes such as infantile undifferentiated round cell sarcomas and primitive myxoid mesenchymal tumors of infancy. BCOR::CCNB3 sarcomas predominantly arise in bone rather than soft tissue and exhibit a higher occurrence in children and adolescent males, whereas sarcomas with BCOR internal tandem duplication show a wider age range but usually arise in the first year of life. Due to their rarity, there is ongoing debate and uncertainty regarding the best treatment approach, with a lack of specific clinical trials addressing these tumors. In this report, we present a unique case of sarcoma with internal tandem duplication of BCOR gene originating in the nasal region. The tumor was successfully and completely resected using the standard VDC-IE chemotherapy protocol, resulting in an unprecedented 100 percent tumor necrosis. The patient has completed the protocol and remains recurrence-free 13 months after diagnosis. This case suggests potential efficacy of the standard VDC-IE protocol in achieving remarkable responses in BCOR rearrangement sarcomas, including the internal tandem duplication subtype. However, further studies are needed to determine the optimal treatment strategies for this disease.